Primary care provider approaches to preventive health delivery: a qualitative study. Issue 5 (8th January 2018) - Murugan, Hemalatha; Spigner, Clarence; McKinney, Christy M.; Wong, Christopher J.
Abstract : Aim: The objective of this study was to seek decision-making insights on the provider level to gain understanding of the values that shape how providers deliver preventive health in the primary care setting. Background: The primary care clinic is a core site for preventive health delivery. While many studies have identified barriers to preventive health, less is known regarding how primary care providers (PCPs) make preventive health decisions such as what services to provide, under what circumstances, and why they might choose one over another. Methods: Qualitative methods were chosen to deeply explore these issues. We conducted semi-structured, one-on-one interviews with 21 PCPs at clinics affiliated with an academic medical center. Interviews with providers were recorded and transcribed. We conducted a qualitative analysis to identify themes and develop a theoretical framework using Grounded Theory methods. Findings: The following themes were revealed: longitudinal care with an established PCP–patient relationship is perceived as integral to preventive health; conflict and doubt accompany non-preventive visits; PCPs defer preventive health for pragmatic reasons; when preventive health is addressed, providers use multiple contextual factors to decide which interventions are discussed; and PCPs desired team-based preventive health delivery, but wish to maintain their role when shared decision-making is required. We present a conceptual framework called Pragmatic Deferral.